Team up! - Liu, Cynthea (Step into reading., 2026)
Toys meet technology when Buzz, Woody, Jessie and the gang meet the electronics preferred by kids today. Their jobs are challenged by these electronics that kids are obsessed with today. Join the original toys as they form a team: Team Bonnie.